Synonymize Arma chinensis as Arma custos based on morphological, molecular and geographical data - Zhao, Qing; Wei, Jiufeng; Bu, Wenjun; Liu, Guoqing; Zhang, Hufang (Zootaxa, 2018)
Arma custos and A. chinensis have a very conspicuous difference in the shape of the pronotal humeral angle, but the genitalic morphological characters are ambiguous and difficult to recognize. The aim of this study was to analyze the taxonomic status of A. chinensis and A. custos based on morphological, molecular, and geographical evidence, and to determine whether DNA barcoding could be a useful additional tool for differentiating similar species. The results clearly demonstrate that A. custos and A. chinensis have not diverged into separate species. So, the following new synonym is proposed: Arma chinensis Fallou, 1881 = Arma custos (Fabricius, 1794) syn. nov.. The results also showed that DNA barcoding using the marker COI can resolve insect taxonomic problems.